Key Attributes of Customer Satisfaction for Shopping Malls Located in Baku, Azerbaijan - Latifova, Vusala (ADA University, 2021)
In recent years, along with economic development and the change in consumer culture, there is a trend that traditional retail stores have been gradually replaced by the shopping malls and shopping centers have become the major venues for consumers these days than in the past. Regardless of the growing importance of contemporary shopping centers in the retail field, the understanding of the shopping mall attributes and their role on consumer satisfaction has not been studied in Baku. The purpose of this study is to analyze the shopping mall attributes from the customers’ perspective and to find out the shopping mall attributes that are the most important sources of customer satisfaction for the modern shopping centers located in Baku. The research conducted in this paper required mixed data collection, both qualitative and quantitative data aligned to the research objectives. The primary data was collected through semistructured interviews with an expert and 6 interview respondents and quantitative survey among 302 respondents. Secondary data in a form of a literature review was used to explore the studies. The study reveals 31 relevant shopping mall attributes as a potential source of customer satisfaction. The result shows that the following shopping center attributes are the most influential ones to customer satisfaction from the consumers’ perspective based on the research conducted in Baku: quality of products, ensured security, general cleaning, atmosphere, and quality of services. The list continuous with the retail mix, cleanliness of food court, cleanliness of sanitary facilities, larger circulation area and accessibility attributes. This research contributes to the literature on contemporary shopping center attributes and customer satisfaction in shopping centers, particularly to the understudied literature in Baku, Azerbaijan. Furthermore, the knowledge of the determinant factors on customer satisfaction may also be beneficial for the companies in the industry and managers to understand the customers’ perceptions, to look at the processes from the customers’ side, and to deliver the desired satisfaction. Throughout the knowledge of determinant factors on customer satisfaction, shopping center management may develop a customer-centric approach which may result in the specific contribution to the individuals as well.
Keywords: Business; Customer service; Customer satisfaction; Shopping mall--Azerbaijan; Shopping mall attribute